HISTOLOGICAL AND HISTOCHEMICAL CHANGES OF THE DAMAGED AREA OF SKIN IN THE DYNAMICS AFTER EXPERIMENTAL THERMAL TRAUMA - Крамар, С.Б.; Волков, К.С.; Kotyk, A.A. (World of Medicine and Biology, 2014)
In experiment on guinea pigs histological and histochemical changes of the damaged area of the skin at different times were studied after severe thermal trauma. It was established that the degree of destructive changes of the epidermis and dermis depends on the period after the burn. Significant vascular disorders and damages of the structural components of connective tissue, changing its histochemical indicators inhibit regenerative processes both in the central and in the marginal area of the wound.